International Tourists Visiting Experiences in Malaysia as Revealed by Travel Bloggers: An Analysis of Travel Blogs Using Tri-component Model of Destination Image - Hashim, Rohani; Omar, Bahiyah; Al-Samarraie, Hosam (Journal of Contemporary Issues in Media & Communication (JCIMC), 2022)
There are numerous travel blogs available for travel bloggers to share their travel experiences with others. Tourists’ feedback in personal blogs have become an important source for acquiring travel information. Evidence shows, however, there is not much research done on the feedback of tourists visiting Malaysia. Therefore, the role of travel bloggers’ feedback in attracting prospective tourists’ attention and how it influenced their decisions to visit Malaysia, became an interesting research question. Based on 50 travel blogs written personally by foreign tourists about Malaysia, an analysis was done specifically to the blog’s content: How the authors perceived Malaysia as a tourist destination and how they motivated prospective tourists were examined to mitigate the above-mentioned gap. In analyzing the text, the Tri-component Model of Destination Image is employed. Results showed that the travel blogs’ content provided detailed, rich and relevant data which included the profiling of the travel bloggers (i.e. visitors of Malaysia), information about their experiences and expectations within their comments. Results showed that the first-hand experience of travel bloggers as depicted in their blogs is a representative of the real thoughts and feelings of tourists, and their positive feedback affected behavioral intentions of potential visitors to visit Malaysia as well as motivated experienced visitors to re-visit the country. By curating positive reviews, Malaysia’s tourism can leverage travel blogs to build positive destination image awareness and increased destination loyalty. The study confirmed that the Tri-component Model of Destination Image is relevant to measure the influence of travel bloggers in motivating prospect visitors to a destination. This paper presented empirical findings on the importance of travel blogs’ for tourism destination image in Malaysia.